Law Changes in Islamic Law (Review of Concepts, Principles and Methodology) - Ahmad Agus Ramdlany, (Technium Social Sciences Journal, 2023)
Changes in law are necessary, both in Western and Islamic law; the basis for changes in Islamic law can be found in sources of Islamic teachings and documented in the history of Islamic law legislation. This article aims to analyze law changes in Islamic teachings, both conceptually, fiqhiyyah principles, and methods that can be followed. The results found that changes in Islamic law have a legitimacy basis from the Prophet's hadith about reformers every 100 years, also reflected in the history of Islamic law legislation both during the time of the Prophet, Companions, Tabi'in, and so on. Changes in law are also recorded from several principles, both fiqhiyyah principles and ushuliyah principles. Social changes influence the change in the law in the community where the law applies and is applied. The method used to change the law is to do ijtihad. The results of this ijtihad in Islamic law can be fatwas, jurisprudence (qadli decisions), doctrines (qaul fukaha), qanuns, and research results.